EMERGING TECHNOLOGIES IN PUBLIC HEALTH CAMPAIGNS: ARTIFICIAL INTELLIGENCE AND BIG DATA - Yvonne Oshevwe Okoro; Oluwatoyin Ayo-Farai; Chinedu Paschal Maduka; Chiamaka Chinaemelum Okongwu; Olamide Tolulope Sodamade (Acta Informatica Malaysia)
This research explores the integration of Artificial Intelligence (AI) and Big Data into public health campaigns, envisioning a future where precision, personalization, and proactive interventions redefine healthcare. Analyzing the transformative potential and challenges, the study examines AI’s role in disease surveillance, diagnostics, and predictive modeling, alongside Big Data’s contributions to personalized interventions and comprehensive health understanding. Ethical considerations, the digital divide, and regulatory frameworks are central challenges, necessitating a delicate balance between innovation and responsibility. The conclusion foresees a healthcare landscape where AI and Big Data enhance the effectiveness of public health campaigns, promising a future characterized by equitable, data-driven, and resilient approaches to address emerging health challenges.